THE REPRESENTATION OF INDONESIAN WOMEN IN CONTEMPORARY TRAVEL WRITING: A STUDY OF DISCOURSE ON GENDER AND TRAVEL WRITING - Akmal Jaya; Mochamad Rizqi Adhi Pratama (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
This research aims to examine the representation of Indonesian women in contemporary travel writings. The rise of globalization has challenged the domination of discourses that tend to place Indonesian women in the subordinate position. However, the challenge does not warrant a symmetrical relation between genders, as it sometimes blurs the relation as a result of clashes between discourses. This study, then, provides an overview of how discourses have shaped the representation of Indonesian women by revealing images that appear explicitly and implicitly in travel stories. Using the Foucauldian discourse analysis approach allowed the writers to exclude subjects, objects, and meanings to discover a comprehensive web of image construction. This research found that Indonesian women’s representation is stuck in an ambiguous position as it strives to be an independent individual subject. Penelitian ini bertujuan untuk menjelaskan representasi perempuan Indonesia melalui cerita perjalanan kontemporer. Pada dasarnya, globalisasi telah menantang kuasa hegemoni wacana yang cenderung menempatkan perempuan Indonesia pada posisi kedua. Akan tetapi, hal tersebut tidak menjamin kesetaraan antara hubungan gender, melainkan terkadang menjadikannya semakin kabur sebagai konsekuensi adanya pertentangan antar wacana. Kajian ini memberikan gambaran bagaimana wacana membentuk representasi perempuan Indonesia dengan menunjukkan citra-citra yang hadir secara eksplisit maupun implisit dalam cerita perjalanan. Dengan menggunakan pendekatan analisis Foucauldian memberikan sebuah kemungkinan kepada kita untuk memisahkan antara subjek, objek dan makna dan untuk menemukan jaring-jaring konstruksi citra yang komprehensif. Penelitian ini menemukan bahwa representasi perempuan Indonesia terjebak dalam posisi yang ambigu yang tampaknya mencoba untuk hadir sebagai subjek independen.